2018
DOI: 10.18632/aging.101449
|View full text |Cite|
|
Sign up to set email alerts
|

Repeated superovulation increases the risk of osteoporosis and cardiovascular diseases by accelerating ovarian aging in mice

Abstract: Superovulation procedures and assisted reproductive technologies have been widely used to treat couples who have infertility problems. Although generally safe, the superovulation procedures are associated with a series of complications, such as ovarian hyper-stimulation syndrome, thromboembolism, and adnexal torsion. The role of long-term repeated superovulation in ovarian aging and especially in associated disorders such as osteoporosis and cardiovascular diseases is still unclear. In this study, we sought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“… 36 One recent study reported that mice exposed to repeated superovulation showed an obvious decrease in the primordial follicle pool and poor oocyte quality. 37 Another study reported ovulation suppression protected against egg aneuploidy in aged female mice. 38 Although the effects of repeated assisted reproduction techniques on ovarian response in humans remain controversial, 39 our findings suggest that the increased risk of repetitive ovarian stimulation on ovarian reserve should be considered in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“… 36 One recent study reported that mice exposed to repeated superovulation showed an obvious decrease in the primordial follicle pool and poor oocyte quality. 37 Another study reported ovulation suppression protected against egg aneuploidy in aged female mice. 38 Although the effects of repeated assisted reproduction techniques on ovarian response in humans remain controversial, 39 our findings suggest that the increased risk of repetitive ovarian stimulation on ovarian reserve should be considered in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that literature supports the notion that the "hazard" or the individual LB probability of each woman within a particular cohort does not remain constant over different treatment cycles. In fact, in mice, repeated superovulation cycles may induce over-expression and over-activation of proteins controlling cell cycle progression in fallopian tubes [22]; alter mitochondrial functions of cumulus cells [23], impair oocyte spindle [23]; and affect ovarian function and decrease the ovarian reserve, fertility, and fecundity [24]. In humans, repeated ovarian stimulation in oocyte donation cycles does not seem to have any adverse effect on number of oocytes collected, oocyte quality, fertilization, preimplantation embryo qualities, and embryo implantation in oocyte recipients [25].…”
Section: Discussionmentioning
confidence: 99%
“…Repeated ovulation promotion increased the number of abnormal mitochondria in mouse oocytes, reduced the volume of the primordial follicular pool, decreased serum AMH levels and significantly inhibited embryo development [ 137 ]. This process also significantly increases the risk of long-term complications such as osteoporosis and cardiovascular disease [ 138 ]. In contrast, oral contraceptives have been shown to alleviate age-related ovarian aging and fertility decline by suppressing ovulation [ 139 ].…”
Section: Factors Related To Os That Lead To Ovarian Agingmentioning
confidence: 99%